Model Tatakelola Grup Rapa’i Daboh Bungong Jeumpa di Kawasan Pengungsian Pasca Tsunami Aceh, CARE - Rika Wirandi; Magfhirah Murni B.P; Berlian Denada (Mahesa Research Center, 2020)
This article aims to determine the form of governance applied in the Rapa'i Daboh Bungong Jeumpa Group (GRDBJ) in the post-Tsunami refugee area in Aceh, CARE, in Jantho City, Aceh Besar District. The problem is focused on the form of GRDBJ governance by using the management function approach reference proposed by Goerge R. Terry. The management function consists of four: 1) Planning (planning); 2) Organizing (organizing); 3) Movement (actuating); and 4) controlling. The research method used in this study is a qualitative research method as a research procedure that produces descriptive data in the form of written words from people and behavior that can be observed using several stages of data collection, namely: observation; literature review; Interview; and documentation. This study concludes that the planning carried out by GRDBJ includes preparing member resources in quality and quantity. In the organizational aspect, GRDBJ has a formal organizational structure that is generally applied in an organization, besides that there is a central and significant role for the caliph and ceh. In the movement, GRDBJ applies work efficiency through optimal utilization of human resources and facilities. In addition, GRDBJ conducts foster group coaching consisting of young children. The form of supervision includes supervision of the performance of members or players, finances, performance materials.